Answer:
The Answer is: y = 2x - 3
Step-by-step explanation:
Given points: (3, 3) and (4, 5)
Find the slope, m:
m = y - y1/(x - x1)
m = 3 - 5/(3 - 4)
m = -2/-1 = 2
Use the Point Slope form of the equation:
y - y1 = m(x - x1)
y - 5 = 2(x - 4)
y - 5 = 2x - 8
y = 2x - 8 + 5
y = 2x - 3
Proof:
f(3) = 2(3) - 3
= 6 - 3 = 3, giving (3, 3)
Step-by-step explanation:
just take from me..your most best and smarties person ever...i don't know the answer
The point of elimination is to have one variable so example
3x + 2y = 4
7X + 3y = 5
1) Try to find a way to have one variable
7(3x + 2y = 4) ----> 21x + 14y = 28
-3(7x+ 3y = 5) -----> -21x -9y = -15
2) add
0 + 5y = 13
3) solve for the last variable
5y = 13
y = 13/5 = 2 3/5 = 2.8
4) Subsitute the variable to get the other one
3x + 2(2.8) = 4
3x + 5.6 = 4
3x = -1.6
x = 0.533333333 (continue)
The intersection would be 0.53 with a line above the 3 and 2.8. (0.5333 , 2.8)
Hope you understand!!
Answer:
the answer for 92-53.3 is 38.7